# Aptitude - Square Root and Cube Root - Discussion

### Discussion :: Square Root and Cube Root - General Questions (Q.No.13)

13. 3 - 1 2 simplifies to: 3

[A].
 3 4
[B].
 4 3
[C].
 4 3
[D]. None of these

Explanation: 3 - 1 2 = (3)2 + 1 2 - 2 x 3 x 1 3 3 3

 = 3 + 1 - 2 3

 = 1 + 1 3

 = 4 3

 Munna said: (Mar 22, 2011) Good caluclation.

 Abhilash said: (Jan 31, 2014) By doing LCM b/w root3 and 1/root3 also we can get that easily.

 Kalaiarasi said: (Nov 27, 2014) How to calculate LCM?

 Amit said: (Feb 20, 2015) It is (a-b)square = (a square+b square-2ab).

 Joslin said: (Apr 5, 2015) Taking LCM. = (sqrt3- 1/sqrt3)^2. = ( (3-1)/sqrt3)^2. = (2/sqrt3)^2. = 4/3.

 Joha said: (Feb 19, 2016) Any one please explain this sum?

 Simi said: (Mar 24, 2016) Use the formula: (a-b)^2 = a^2 + b^2 - 2(a*b).

 Yash Badgujar said: (Jul 15, 2016) = sqrt3/1 - 1/sqrt3. = sqrt9 - 1/sqrt3. = (3 - 1/sqrt3)^2. We know that, (a/b)^2 = a^2/b^2. so, = (2^2)/(sqrt3^2). = 4/sqrt9. = 4/3.

 Aswin said: (Jul 26, 2018) In this sum, why don't we use BODMAS condition?